Program Service Learning Untuk Peningkatan Kompetensi Mahasiswa Program Studi Pendidikan Bahasa Inggris: Manfaat dan Tantangan - Siti Amsiyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2018)
Despite its popularity in universities in developed countries, service learning as a program that integrates teaching-learning and community services is not yet popular in Indonesia. This qualitative research aims to explore the benefits and challenges faced by students of English Education Department at UINSA doing service learning. The data were collected using self-reported measures from 46 students’ reflective papers about their taking parts in 12 Islamic primary schools in the suburban areas in Surabaya. These schools have some limitations in terms of number of teachers and teaching-learning facilities. Some benefits reflected by the students include the development of their pedagogical and personal development. The challenges relate to issues of time and geographical location of the school, differences between the classroom concepts and real life context and dual position of the students at school as a learning community. Considering students’ positive reflection on the program, service learning should be integrated in every course to better develop students’ competencies.